2019
DOI: 10.3389/fcimb.2018.00451
|View full text |Cite
|
Sign up to set email alerts
|

Differing Virulence of Healthy Skin Commensals in Mouse Models of Infection

Abstract: Introduction: As therapies for atopic dermatitis (AD) based on live biotherapeutic products (LBP) are developed, the potential displacement of biotherapeutic strains, and species to mucosal sites where they are not naturally found is of investigative interest. However, formal assessment of the toxicity potential of healthy skin commensal organisms has not been reported in the literature. Our previous research indicates that topical application of live Roseomonas mucosa to treat AD was associated with clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…3, G and H) was similar to the culture yields from patients with AD after treatment (Fig. 3F) and healthy controls (25).…”
Section: R Mucosa Treatment Is Associated With Modest Shifts In Skin ...supporting
confidence: 77%
See 1 more Smart Citation
“…3, G and H) was similar to the culture yields from patients with AD after treatment (Fig. 3F) and healthy controls (25).…”
Section: R Mucosa Treatment Is Associated With Modest Shifts In Skin ...supporting
confidence: 77%
“…Coisolation of R. mucosa with quintessential catheter pathogens like S. aureus in these studies additionally suggested a low virulence potential for R. mucosa given the recognized pathogenic potential of S. aureus. Safety claims for R. mucosa are further supported by the failure of RmHV to generate notable pathology or infection after direct inoculation into the eyes, lungs, stomach, and veins of mice, in contrast to the morbidity and mortality seen with other skin commensals from healthy volunteers (3,25). Thus, R. mucosa has yet to fulfill Koch's postulates for defining agents that cause infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Yet even in the absence of resistance, antibiotics have not been shown to improve the symptoms of AD, and treatment guidelines explicitly recommend against the use of topical or oral antibiotics unless clinical signs of frank cellulitis are present 3,14 . Furthermore, attempting to curtail S. aureus through topical use of CoNS‐containing probiotics 3 presents an experimental risk of infecting patients with the treatment strain 15 …”
Section: Figurementioning
confidence: 99%
“… 3 , 14 Furthermore, attempting to curtail S. aureus through topical use of CoNS‐containing probiotics 3 presents an experimental risk of infecting patients with the treatment strain. 15 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation